Using the Fathers - Reno, R. R. (Journal of theological interpretation, 2013)
Scholarly study of the biblical exegesis of the church fathers has increased significantly. However, authors of contemporary commentaries are little influenced by patristic exegesis. This lack of influence flows from a number of factors. Most commentaries are written by biblical scholars who are formed by the modern tradition of historical-critical analysis. The few theologians who write commentaries have their own modern habits of mind that tend toward conceptual abstraction. Both types of modern scholar tend to make different assumptions about the Bible and the purposes of exegesis than did the church fathers. Recovering the exegetical genius of the church fathers requires adopting their assumptions, as least in part. This is as much a spiritual as an intellectual challenge.